Sexshop: Trends and perceptions among university students - Daniel Ruiz - Madeline Melchor (GEON Journal (Management, Organizations and Business), 2015)
The concept of sexuality has changed over time and new behaviors focused on diversity, which can be reflected for example in opening shops sex shops that sell sex toys. This research explores the cognitive perceptions and attitudes regarding practices related to buying behavior among university students Sexshop shops. We worked through a mixed approach in two Qualitative stages (focus group) - Quantitative (questionnaire) finding that much of the segment under study are comfortable talking about sexuality, there is a greater perception of sex toy use by women and advertising in business should be reconsidered its little impact.
Keywords: Sexshop; Sex toys; Perception